Performance of a highly successful outbreak strain of Mycobacterium tuberculosis in a multifaceted approach to bacterial fitness assessment - Yokobori, Noemi (2018)
Fil: Yokobori, Noemí. Consejo Nacional de Investigaciones Científicas y Técnicas de Argentina. Academia Nacional de Medicina. Instituto de Medicina Experimental (IMEX), Buenos Aires; Argentina.